Resin composition
The resin composition, featuring a specific organic solvent, thermosetting resin, and high inorganic filler content, addresses the issue of unevenness after lamination in printed wiring boards, enhancing their reliability and performance.
Patent Information
- Application Number
- JP2022016388
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-02-04
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-02-04
AI Technical Summary
Existing resin compositions used in the build-up method for manufacturing printed wiring boards often suffer from unevenness after lamination, which affects the reliability and performance of the boards.
A resin composition comprising an organic solvent with a solubility in water at 20°C of 0.6 g/L or more and less than 15 g/L, a thermosetting resin, and an inorganic filler, where the organic solvent content is 35% or more by mass and the inorganic filler content is 40% or more by mass.
The proposed resin composition effectively suppresses the occurrence of unevenness after lamination, leading to improved reliability and performance of printed wiring boards.
Smart Images

Figure 0007647617000001 
Figure 0007647617000002 
Figure 0007647617000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition containing a thermosetting resin, and further to a method for producing a resin sheet and a method for producing a printed wiring board using the resin composition. [Background technology]
[0002] A known manufacturing technique for printed wiring boards is a build-up manufacturing method in which insulating layers and conductor layers are alternately stacked. In build-up manufacturing methods, the insulating layer is generally formed by curing a resin composition containing a thermosetting resin and an inorganic filler. It has been known that the thermal expansion coefficient can be reduced by increasing the filling rate of the inorganic filler in the insulating layer, and that the reliability of electronic components can be improved by using a printed wiring board having such an insulating layer (Patent Document 1).
[0003] When the inorganic filler is highly filled, the solvent used to knead the inorganic filler with the thermosetting resin has a significant effect on the fluidity and unevenness of the insulating layer that is formed, so the selection of the solvent is extremely important. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-229840 A Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide a resin composition capable of suppressing the occurrence of unevenness after lamination (see Test Example 2 for the unevenness after lamination). [Means for solving the problem]
[0006] Means for Solving the Problems of the Invention The present inventors conducted extensive research in order to achieve the objects of the present invention, and unexpectedly discovered that by incorporating a certain amount or more of (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L in a resin composition containing (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, it is possible to suppress the occurrence of unevenness after lamination, and thus completed the present invention.
[0007] That is, the present invention includes the following. [1] A resin composition comprising (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, The component (A) contains (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L, The content of the (A1) component is 35% by mass or more, relative to 100% by mass of the (A) component in the resin composition; A resin composition, wherein the content of the component (C) is 40% by mass or more, relative to 100% by mass of the components other than the component (A) in the resin composition. [2] The resin composition according to the above [1], wherein the component (A1) contains an organic solvent having a boiling point of 130°C to 200°C at 760 mmHg. [3] The resin composition according to the above [1] or [2], wherein the component (A1) contains an organic solvent selected from the group consisting of ketone-based solvents, ester-based solvents, and glycol ether ester-based solvents. [4] The resin composition according to any one of the above [1] to [3], wherein the component (A) further contains (A2) an organic solvent having a solubility in water at 20°C of 15 g / L or more and less than 150 g / L. [5] The resin composition according to the above [4], wherein the component (A2) contains a ketone-based solvent. [6] The resin composition according to any one of the above [1] to [5], wherein the component (A) further contains (A3) an organic solvent having a solubility in water at 20°C of less than 0.6 g / L. [7] The resin composition according to any one of the above [1] to [6], wherein the component (A) further contains (A4) an organic solvent having a solubility in water at 20° C. of 150 g / L or more. [8] The resin composition according to any one of the above [1] to [7], wherein the component (B) contains an epoxy resin. [9] The resin composition according to the above [8], wherein the component (B) further contains an active ester-based curing agent.
[10] The resin composition according to the above [8] or [9], wherein the component (B) further contains a phenol-based curing agent.
[11] A cured product of the resin composition according to any one of [1] to
[10] above.
[12] A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of the above [1] to
[11] .
[13] A semiconductor device comprising the printed wiring board according to
[12] above.
[14] A support; A resin composition layer formed on the support and made of a resin composition containing (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, The component (A) contains (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L, The content of the (A1) component is 35% by mass or more, relative to 100% by mass of the (A) component in the resin composition; a resin composition layer having a content of the component (C) of 40% by mass or more, when the components other than the component (A) in the resin composition are taken as 100% by mass; A resin sheet having the above structure.
[15] A method for producing a printed wiring board, comprising the following steps (I) and (II): (I) A step of laminating the resin sheet described in the above
[14] so that the layer of the resin composition of the resin sheet is bonded to the inner layer substrate. (II) A step of curing the layer of the resin composition to form an insulating layer. Effect of the Invention
[0008] According to the resin composition of the present invention, the occurrence of unevenness after lamination can be suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.
[0010] <Resin composition> The resin composition of the present invention comprises (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, the (A) component comprises (A1) an organic solvent having a solubility in water of 0.6 g / L or more and less than 15 g / L at 20° C., the content of the (A1) component is 35% by mass or more when the (A) component in the resin composition is taken as 100% by mass, and the content of the (C) component is 40% by mass or more when the components other than the (A) component in the resin composition are taken as 100% by mass. With such a resin composition, it is possible to suppress the occurrence of unevenness after lamination.
[0011] The resin composition of the present invention may further contain optional components in addition to (A) the organic solvent, (B) the thermosetting resin, and (C) the inorganic filler, such as (D) a flame retardant, (E) a thermoplastic resin, (F) a curing accelerator, and (G) other additives.
[0012] In one embodiment, the resin composition of the present invention may be in a varnish state before drying before processing into a resin sheet. The term "varnish state" refers to a state in which non-particulate non-volatile components among the non-volatile components contained in the resin composition are dissolved in a solvent. In one embodiment, the varnish-like resin composition can be applied and is preferably fluid. The resin sheet to be laminated on the substrate includes a layer of a film-like resin composition formed by drying the varnish-like resin composition.
[0013] Each component contained in the resin composition will be described in detail below.
[0014] <(A) Organic solvent> The resin composition of the present invention contains (A) an organic solvent. The (A) organic solvent described here is a liquid compound having a boiling point of 250°C or less (a compound that is liquid at 20°C or less) that does not contain carbon-carbon double bonds and carbon-carbon triple bonds (excluding bonds that constitute aromatic rings) in the molecule composed of skeletal atoms selected from carbon atoms and oxygen atoms. The (A) organic solvent described here does not include those that fall under (B) thermosetting resins. In this specification, the boiling point refers to the boiling point at 760 mmHg (i.e., the standard boiling point) unless otherwise specified. The (A) organic solvent may be used alone or in combination of two or more types.
[0015] The (A) organic solvent includes (A1) an organic solvent having a solubility in water of 0.6 g / L or more and less than 15 g / L at 20° C. The (A1) component may be used alone or in combination of two or more types.
[0016] The solubility of the (A1) component in water at 20°C (hereinafter sometimes abbreviated as "water solubility") is preferably 1 g / L or more and less than 14 g / L, more preferably 2 g / L or more and less than 13 g / L, even more preferably 3 g / L or more and less than 12 g / L, and particularly preferably 4 g / L or more and less than 11 g / L.
[0017] In one embodiment, the component (A1) preferably contains an organic solvent having a boiling point at 760 mmHg (hereinafter sometimes simply referred to as "boiling point") of 100°C to 230°C, more preferably an organic solvent having a boiling point of 130°C to 200°C, even more preferably an organic solvent having a boiling point of 140°C to 195°C, and particularly preferably an organic solvent having a boiling point of 150°C to 190°C.
[0018] Specific examples of the component (A1) include ketone-based solvents such as 2-heptanone (MAK) (boiling point 151°C); ester-based solvents such as cyclohexanol acetate (CHXA) (boiling point 173°C); glycol ether ester-based solvents such as ethylene glycol monobutyl ether acetate (BMGAC) (boiling point 188°C); and glycol diether-based solvents such as dipropylene glycol methyl-n-butyl ether (DPMNB) (boiling point 227°C) aromatic hydrocarbon-based solvents. In one embodiment, the component (A1) preferably contains an organic solvent selected from the group consisting of ketone-based solvents, ester-based solvents, and glycol ether ester-based solvents, and particularly preferably contains an organic solvent selected from the group consisting of MAK, CHXA, and BMGAC.
[0019] In one embodiment, the content of the (A1) component in the (A) organic solvent may differ between the varnish-like resin composition before drying and processing into a resin sheet and the resin composition after drying in the resin sheet to be laminated onto a substrate.
[0020] The content of the (A1) component in the (A) organic solvent in the resin composition before drying is 35% by mass or more, preferably 50% by mass or more, more preferably 53% by mass or more, even more preferably 55% by mass or more, and particularly preferably 57% by mass or more, when the (A) organic solvent in the resin composition is 100% by mass. The upper limit is not particularly limited, but is, for example, 100% by mass or less, preferably 90% by mass or less, more preferably 80% by mass or less, even more preferably 70% by mass or less, and particularly preferably 60% by mass or less.
[0021] The content of the (A1) component in the (A) organic solvent in the resin composition after drying is 35% by mass or more, preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and particularly preferably 75% by mass or more, when the (A) organic solvent in the resin composition is 100% by mass. The upper limit is not particularly limited, but is, for example, 100% by mass or less, preferably 95% by mass or less, and particularly preferably 90% by mass or less.
[0022] In one embodiment, the (A) organic solvent preferably further contains (A2) an organic solvent having a solubility in water of 15 g / L or more and less than 150 g / L at 20° C. The (A2) component may be used alone or in combination of two or more types.
[0023] The solubility of the (A2) component in water at 20°C (water solubility) is preferably 18 g / L or more and less than 100 g / L, more preferably 20 g / L or more and less than 70 g / L, even more preferably 22 g / L or more and less than 50 g / L, and particularly preferably 24 g / L or more and less than 30 g / L.
[0024] In one embodiment, the component (A2) preferably contains an organic solvent having a boiling point at 760 mmHg of 75°C to 230°C, more preferably an organic solvent having a boiling point of 75°C to 200°C, even more preferably an organic solvent having a boiling point of 75°C to 180°C, and particularly preferably an organic solvent having a boiling point of 75°C to 160°C.
[0025] Specific examples of the component (A2) include ketone-based solvents such as cyclohexanone (Anone) (boiling point 156°C), methyl ethyl ketone (MEK) (boiling point 80°C), and methyl isobutyl ketone (boiling point 116°C); ester-based solvents such as ethyl acetate (AE) (boiling point 77°C), isopropyl acetate (IPAC) (boiling point 85°C), propyl acetate (NPAC) (boiling point 102°C), and butyl acetate (BA) (boiling point 126°C); 3-methoxybutyl acetate (MBA) (boiling point 171°C), diethylene glycol monoacetate (DMBA) (boiling point 172°C), and butyl acetate (BA) (boiling point 171°C). Examples of suitable solvents include glycol ether ester solvents such as dipropylene glycol methyl-n-propyl ether (DPMNP) (boiling point 203°C); and glycol diether solvents such as propylene glycol diacetate (PGDA) (boiling point 190°C), 1,4-butanediol diacetate (1,4-BDDA) (boiling point 232°C), and 1,3-butylene glycol diacetate (1,3-BGDA) (boiling point 232°C). In one embodiment, the component (A2) preferably contains a ketone solvent, and particularly preferably contains an organic solvent selected from the group consisting of Anone and MEK.
[0026] In one embodiment, the content of the (A2) component in the (A) organic solvent may differ between the varnish-like resin composition before drying and processing into a resin sheet and the resin composition after drying in the resin sheet to be laminated onto a substrate.
[0027] The content of the (A2) component in the (A) organic solvent in the resin composition before drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.1 mass% or more, preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and particularly preferably 15 mass% or more, and the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 40 mass% or less, more preferably 35 mass% or less, even more preferably 30 mass% or less, and particularly preferably 25 mass% or less.
[0028] The content of the (A2) component in the (A) organic solvent in the resin composition after drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.1 mass% or more, preferably 1 mass% or more, and particularly preferably 5 mass% or more, and the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 40 mass% or less, more preferably 30 mass% or less, and particularly preferably 20 mass% or less.
[0029] In one embodiment of the resin composition of the present invention, it is preferable that the (A) organic solvent further contains (A3) an organic solvent having a solubility in water of less than 0.6 g / L at 20° C. The (A3) component may be used alone or in combination of two or more kinds.
[0030] In one embodiment, the component (A3) preferably contains an organic solvent having a boiling point at 760 mmHg of 50°C to 230°C, more preferably an organic solvent having a boiling point of 80°C to 200°C, even more preferably an organic solvent having a boiling point of 90°C to 150°C, and particularly preferably an organic solvent having a boiling point of 100°C to 130°C.
[0031] Specific examples of the (A3) component include aromatic hydrocarbon solvents such as toluene (boiling point 110°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), and ethylbenzene (boiling point 136°C); and aliphatic hydrocarbon solvents such as n-pentane (boiling point 36°C), n-hexane (boiling point 69°C), 2-methylpentane (also known as isohexane) (boiling point 60-62°C), n-heptane (boiling point 98°C), n-octane (boiling point 125°C), cyclopentane (boiling point 49°C), cyclohexane (boiling point 81°C), methylcyclohexane (boiling point 101°C), and ethylcyclohexane (boiling point 132°C). In one embodiment, the (A3) component preferably contains an aromatic hydrocarbon solvent, and particularly preferably contains toluene.
[0032] In one embodiment, the content of the (A3) component in the (A) organic solvent may differ between the varnish-like resin composition before drying and processing into a resin sheet and the resin composition after drying in the resin sheet to be laminated onto a substrate.
[0033] The content of the (A3) component in the (A) organic solvent in the resin composition before drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 5 mass% or more, and particularly preferably 10 mass% or more, and the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 40 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 15 mass% or less.
[0034] The content of the (A3) component in the (A) organic solvent in the resin composition after drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 1 mass% or more, and particularly preferably 3 mass% or more; the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 40 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 10 mass% or less.
[0035] In one embodiment of the resin composition of the present invention, it is preferable that the (A) organic solvent further contains (A4) an organic solvent having a solubility in water of 150 g / L or more at 20° C. The (A4) component may be used alone or in combination of two or more.
[0036] In one embodiment, the component (A4) preferably contains an organic solvent having a boiling point at 760 mmHg of 50°C to 230°C, more preferably an organic solvent having a boiling point of 70°C to 200°C, even more preferably an organic solvent having a boiling point of 90°C to 150°C, and particularly preferably an organic solvent having a boiling point of 110°C to 130°C.
[0037] Specific examples of the component (A4) include ester-based solvents such as γ-butyrolactone (GBL) (boiling point 204° C.) and methyl acetate (MA) (boiling point 56° C.); glycol ether ester-based solvents such as propylene glycol monomethyl ether acetate (PGMEA) (boiling point 146° C.), diethylene glycol monoethyl ether acetate (EDGAC) (boiling point 217° C.), and dipropylene glycol methyl ether acetate (DPMA) (boiling point 213° C.); glycol diether-based solvents such as dipropylene glycol dimethyl ether (DMM) (boiling point 175° C.); diethylene glycol monobutyl ether (DB) (boiling point 231° C.), propylene glycol monomethyl Examples of suitable glycol monoether solvents include propylene glycol monomethyl ether (MMPG) (boiling point 121°C), 3-methoxybutanol (MB) (boiling point 161°C), and propylene glycol monomethyl ether (PGM) (boiling point 120°C); glycol solvents such as 1,3-butylene glycol (1,3-BG) (boiling point 208°C); alcohol solvents such as methanol (boiling point 64°C), ethanol (boiling point 78°C), n-propanol (boiling point 97°C), and isopropanol (boiling point 82°C); and amide solvents such as N,N-dimethylformamide (DMF) (boiling point 153°C), N,N-dimethylacetamide (DMA) (boiling point 165°C), and N-methyl-2-pyrrolidone (NMP) (boiling point 202°C). In one embodiment, the component (A4) preferably contains a glycol monoether solvent, and particularly preferably contains PGM.
[0038] In one embodiment, the content of the (A4) component in the (A) organic solvent may differ between the varnish-like resin composition before drying and processing into a resin sheet, and the resin composition after drying in the resin sheet to be laminated onto a substrate.
[0039] The content of the (A4) component in the (A) organic solvent in the resin composition before drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 3 mass% or more, and particularly preferably 5 mass% or more, and the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less, and particularly preferably 10 mass% or less.
[0040] The content of the (A4) component in the (A) organic solvent in the resin composition after drying, when the (A) organic solvent in the resin composition is taken as 100 mass%, is not particularly limited, but is, for example, 0 mass% or more, 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 1 mass% or more, and particularly preferably 3 mass% or more; the upper limit is 50 mass% or less, and is not particularly limited, but is preferably 40 mass% or less, more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 10 mass% or less.
[0041] In one embodiment, the content of the (A) component in the resin composition may differ between the varnish-like resin composition before drying and processing into a resin sheet and the resin composition after drying in the resin sheet to be laminated to a substrate.
[0042] The content of component (A) in the resin composition before drying, when all components in the resin composition are taken as 100 mass%, is not particularly limited, but is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and particularly preferably 15 mass% or more; the upper limit is not particularly limited, but is preferably 60 mass% or less, more preferably 50 mass% or less, even more preferably 40 mass% or less, and particularly preferably 35 mass% or less.
[0043] The content of component (A) in the resin composition after drying, when all components in the resin composition are taken as 100 mass%, is not particularly limited, but is preferably 10 mass% or less, more preferably 8 mass% or less, even more preferably 6 mass% or less, and particularly preferably 5 mass% or less; the upper limit is not particularly limited, but is preferably 0.1 mass% or more, more preferably 0.2 mass% or more, even more preferably 0.5 mass% or more, and particularly preferably 1 mass% or more.
[0044] <(B) Thermosetting resin> The resin composition of the present invention contains a thermosetting resin (B). Examples of the thermosetting resin (B) include epoxy resins, epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, polyimide resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, and silicone resins, and may also contain a curing agent (e.g., an epoxy resin curing agent) that can react with them to cure them.
[0045] The content of the (B) thermosetting resin in the resin composition is not particularly limited, but is preferably 60% by mass or less, more preferably 55% by mass or less, even more preferably 50% by mass or less, and particularly preferably 45% by mass or less, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass. The lower limit of the content of the (B) thermosetting resin in the resin composition is, for example, 0% by mass or more, 1% by mass or more, preferably 5% by mass or more, more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass.
[0046] <(B1) Epoxy resin> The resin composition of the present invention preferably contains (B1) epoxy resin as (B) thermosetting resin. (B1) epoxy resin is a curable resin having an epoxy group and an epoxy equivalent of 5,000 g / eq. or less. (B1) epoxy resin described here is a component other than those corresponding to (E) thermoplastic resin described below.
[0047] (B1) Examples of the epoxy resin include bixylenol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol AF type epoxy resin, dicyclopentadiene type epoxy resin, trisphenol type epoxy resin, naphthol novolac type epoxy resin, phenol novolac type epoxy resin, tert-butyl-catechol type epoxy resin, naphthalene type epoxy resin, naphthol type epoxy resin, anthracene type epoxy resin, glycidylamine type epoxy resin, glycidyl ether ... Examples of the epoxy resin include ester type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, linear aliphatic epoxy resin, epoxy resin having a butadiene structure, alicyclic epoxy resin, heterocyclic epoxy resin, spiro ring-containing epoxy resin, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, naphthylene ether type epoxy resin, trimethylol type epoxy resin, tetraphenylethane type epoxy resin, isocyanurate type epoxy resin, phenolphthalimidine type epoxy resin, etc. The (B1) epoxy resin may be used alone or in combination of two or more kinds.
[0048] The resin composition of the present invention preferably contains, as the epoxy resin (B1), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the epoxy resin (B1) is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.
[0049] (B1) Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only liquid epoxy resins as epoxy resins, or only solid epoxy resins, or both liquid and solid epoxy resins, but it is particularly preferable that the resin composition contains both liquid and solid epoxy resins.
[0050] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.
[0051] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred.
[0052] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "jER828EL", "828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" ( bisphenol F type epoxy resin; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX; "EX-991L" (alkyleneoxy and butadiene type epoxy resin) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with ester structure) manufactured by Daicel ); "PB-3600" manufactured by Daicel Corporation, "JP-100" and "JP-200" manufactured by Nippon Soda Co., Ltd. (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.
[0053] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.
[0054] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.
[0055] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; "EXA-7311" and "E XA-7311-G3, EXA-7311-G4, EXA-7311-G4S, HP6000, HP6000L (naphthylene ether type epoxy resin); EPPN-502H (trisphenol type epoxy resin) manufactured by Nippon Kayaku; NC7000L (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku; NC3000H, NC3000, NC3000L, NC3000FH, NC3100 (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material; ESN475V manufactured by Nippon Steel Chemical & Material; "ESN4100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YL7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.
[0056] When a solid epoxy resin and a liquid epoxy resin are used in combination as the (B1) epoxy resin, the mass ratio thereof (solid epoxy resin:liquid epoxy resin) is preferably 10:1 to 1:50, more preferably 5:1 to 1:20, and particularly preferably 2:1 to 1:10.
[0057] The epoxy equivalent of the (B1) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.
[0058] The weight average molecular weight (Mw) of the epoxy resin (B1) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and even more preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.
[0059] The content of the (B1) epoxy resin in the resin composition is not particularly limited, but is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, and particularly preferably 30% by mass or less, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass. The lower limit of the content of the (B1) epoxy resin in the resin composition is not particularly limited, but is, for example, 0% by mass or more, 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 5% by mass or more, even more preferably 10% by mass or more, and particularly preferably 15% by mass or more, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass.
[0060] <(B2) Epoxy resin hardener> When the resin composition of the present invention contains an epoxy resin (B1) as the thermosetting resin (B), it may further contain an epoxy resin curing agent (B2) as an optional component. The epoxy resin curing agent (B2) may be used alone or in any combination of two or more. When the epoxy resin (B1) is contained as the thermosetting resin (B), the epoxy resin curing agent (B2) may have a function of reacting with the epoxy resin (B1) to cure it. The epoxy resin curing agent (B2) described here is a component other than the flame retardant (D) and thermoplastic resin (E) described below.
[0061] The (B2) epoxy resin curing agent is not particularly limited, and examples thereof include active ester curing agents, phenolic curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents. In one embodiment, the (B2) epoxy resin curing agent ((B) thermosetting resin) preferably contains one or more epoxy resin curing agents selected from active ester curing agents, phenolic curing agents, and cyanate ester curing agents, and more preferably contains one or more epoxy resin curing agents selected from active ester curing agents and phenolic curing agents. In one embodiment, the (B2) epoxy resin curing agent ((B) thermosetting resin) particularly preferably contains an active ester curing agent from the viewpoint of further reducing the dielectric tangent. In one embodiment, the (B2) epoxy resin curing agent ((B) thermosetting resin) particularly preferably contains a phenolic curing agent from the viewpoint of further improving the curability.
[0062] As the active ester curing agent, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.
[0063] Specifically, the active ester curing agent is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, or an active ester compound containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferable.
[0064] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8150-62T". and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds which are benzoylated products of phenol novolac, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation), etc.
[0065] As the phenol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the adherend, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac resin is preferable. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "KA-1160" manufactured by DIC Corporation.
[0066] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). ; polycarbodiimides such as aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].
[0067] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.
[0068] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.
[0069] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.
[0070] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.
[0071] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.
[0072] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.
[0073] The reactive group equivalent of the epoxy resin curing agent (B2) is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the epoxy resin curing agent (B2) per equivalent of reactive group.
[0074] When an active ester curing agent is included as the epoxy resin curing agent (B2), the content of the active ester curing agent in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, and particularly preferably 7% by mass or more, from the viewpoint of suppressing the dielectric tangent lower, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass. Also, the content of the active ester curing agent in the resin composition is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and particularly preferably 50% by mass or more, from the viewpoint of suppressing the dielectric tangent lower, when the (B2) epoxy resin curing agent in the resin composition is taken as 100% by mass.
[0075] In the case where a phenol-based curing agent is contained as the (B2) epoxy resin curing agent, the content of the phenol-based curing agent in the resin composition is preferably 0.5 mass% or more, more preferably 1 mass% or more, and particularly preferably 1.5 mass% or more, from the viewpoint of further improving the curability, when the components other than the (A) organic solvent in the resin composition are taken as 100 mass%.
[0076] The content of the epoxy resin curing agent (B2) in the resin composition is not particularly limited, but is preferably 30% by mass or less, more preferably 25% by mass or less, even more preferably 20% by mass or less, and particularly preferably 15% by mass or less, when the components other than the organic solvent (A) in the resin composition are taken as 100% by mass. The lower limit of the content of the epoxy resin curing agent (B2) in the resin composition is not particularly limited, but may be, for example, 0% by mass or more, 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, when the components other than the organic solvent (A) in the resin composition are taken as 100% by mass.
[0077] <(C) Inorganic filler> The resin composition of the present invention contains an inorganic filler (C). The inorganic filler (C) is contained in the resin composition in the form of particles.
[0078] (C) An inorganic compound is used as the material of the inorganic filler. (C) Examples of the material of the inorganic filler include silica, alumina, aluminosilicate, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica or aluminosilicate is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (C) inorganic filler may be used alone or in combination of two or more kinds in any ratio.
[0079] Examples of commercially available (C) inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", and "YA010C" manufactured by Admatechs Co., Ltd.; "UFP-30" manufactured by Denka Company; "Silfill NSS-3N", "Silfill NSS-4N", and "Silfill NSS-5N" manufactured by Tokuyama Corporation; "SC2500", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "DAW-03" and "FB-105FD" manufactured by Denka Company; "BA-S" manufactured by JGC Catalysts and Chemicals Co., Ltd.; and "MG-005" manufactured by Taiheiyo Cement Corporation.
[0080] The average particle size of the (C) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 4 μm or less, even more preferably 3 μm or less, and particularly preferably 2 μm or less. The lower limit of the average particle size of the (C) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.03 μm or more, even more preferably 0.05 μm or more, and particularly preferably 0.07 μm or more. The average particle size of the (C) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.
[0081] The specific surface area of the (C) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of the inorganic filler (C) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.
[0082] The (C) inorganic filler may be a solid inorganic filler with an average porosity of 0 volume% (preferably solid silica, solid alumina, solid aluminosilicate), may be a hollow inorganic filler with an average porosity of more than 0 volume% (preferably hollow silica, hollow alumina, hollow aluminosilicate), or may contain both. From the viewpoint of lowering the dielectric constant, the (C) inorganic filler preferably contains only a hollow inorganic filler, or contains both a solid inorganic filler and a hollow inorganic filler. The average porosity of the hollow inorganic filler is preferably 90 volume% or less, more preferably 85 volume% or less. The lower limit of the average porosity of the hollow inorganic filler is not particularly limited, but may be, for example, more than 0 volume%, 1 volume% or more, 5 volume% or more, 10 volume% or more, 20 volume% or more, 30 volume% or more, etc. The porosity P (volume %) of an inorganic filler is defined as the volume ratio of the total volume of one or more voids present inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of voids / volume of particle). For example, the measured value of the actual density of the inorganic filler D M (g / cm 3 ), and the theoretical value of the material density of the material forming the inorganic filler D T (g / cm 3 ) is used to calculate according to the following formula (I).
[0083]
number
[0084] The actual density of the inorganic filler can be measured, for example, by using a true density measuring device. Examples of the true density measuring device include ULTRAPYCNOMETER 1000 manufactured by QUANTACHROME Co., Ltd. As the measurement gas, for example, nitrogen is used.
[0085] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane, an organosilazane compound, and a titanate coupling agent. The surface treatment agent may be used alone or in any combination of two or more.
[0086] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).
[0087] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.
[0088] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition or the melt viscosity in the form of a sheet, it is more preferable that the melt viscosity is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:
[0089] (C) The amount of carbon per unit surface area of the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.
[0090] The content (mass%) of the inorganic filler (C) in the resin composition is 40% by mass or more, preferably 50% by mass or more, more preferably 55% by mass or more, even more preferably 60% by mass or more, even more preferably 65% by mass or more, and particularly preferably 70% by mass or more, when the components other than the organic solvent (A) in the resin composition are taken as 100% by mass. The upper limit of the content (mass%) of the inorganic filler (C) in the resin composition is not particularly limited, but may be preferably 90% by mass or less, more preferably 85% by mass or less, even more preferably 80% by mass or less, and particularly preferably 78% by mass or less, when the components other than the organic solvent (A) in the resin composition are taken as 100% by mass.
[0091] The content (volume %) of the inorganic filler (C) in the resin composition is preferably 30% by volume or more, more preferably 35% by volume or more, even more preferably 40% by volume or more, even more preferably 45% by volume or more, and particularly preferably 50% by volume or more, when the components other than the organic solvent (A) in the resin composition are taken as 100% by volume. The upper limit of the content (volume %) of the inorganic filler (C) in the resin composition is not particularly limited, but when the components other than the organic solvent (A) in the resin composition are taken as 100% by volume, it may be preferably 80% by volume or less, more preferably 75% by volume or less, even more preferably 70% by volume or less, and particularly preferably 65% by volume or less.
[0092] <(D) Flame retardant> The resin composition of the present invention may contain a flame retardant (D) as an optional component. The flame retardant (D) described here is a component other than the curing accelerator (F) described below.
[0093] Examples of the (D) flame retardant include phosphorus-based flame retardants such as phosphazene compounds, phosphates, phosphoric acid esters, polyphosphates, phosphinates, phosphinic acid esters, phosphonates, and phosphonic acid esters; nitrogen-based flame retardants such as aliphatic amine compounds, aromatic amine compounds, nitrogen-containing heterocyclic compounds, and urea compounds; inorganic flame retardants such as metal hydroxides such as magnesium hydroxide and aluminum hydroxide, and antimony compounds such as antimony trioxide, antimony pentoxide, and sodium antimonate; and halogen-based flame retardants such as hexabromobenzene, chlorinated paraffin, brominated polycarbonate resins, brominated epoxy resins, brominated phenoxy resins, brominated polyphenylene ether resins, brominated polystyrene resins, and brominated benzyl polyacrylate resins. The (D) flame retardants may be used alone or in combination of two or more.
[0094] In the resin composition of the present invention, the (D) flame retardant preferably contains a phosphorus-based flame retardant; more preferably contains a phosphorus-based flame retardant selected from the group consisting of phosphazenes, phosphates, phosphoric acid esters, polyphosphates, phosphinates, phosphinic acid esters, phosphonates, and phosphonic acid esters; particularly preferably contains a phosphinic acid ester.
[0095] Examples of phosphazenes include phenoxycyclophosphazenes such as hexaphenoxycyclotriphosphazene, tris(4-hydroxyphenoxy)triphenoxycyclotriphosphazene, hexakis(4-hydroxyphenoxy)cyclotriphosphazene, tris(4-methylphenoxy)triphenoxycyclotriphosphazene, tris(4-cyanophenoxy)triphenoxycyclotriphosphazene, hexakis(4-aminophenoxy)cyclotriphosphazene, tris[4-(2-glycidyloxyethyl)phenoxy]triphenoxycyclotriphosphazene, and octaphenoxycyclotetraphosphazene.
[0096] Examples of phosphates include ammonium phosphate, melamine phosphate, and piperazine phosphate.
[0097] Examples of the phosphate ester include non-halogenated aliphatic phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, and trioctyl phosphate; triphenyl phosphate, cresyl diphenyl phosphate, dicresyl phenyl phosphate, tricresyl phosphate, tris(2,6-dimethylphenyl)phosphate, tris(4-isopropylphenyl)phosphate, tris(4-tert-butylphenyl)phosphate, and bis(4-tert-butylphenyl)phosphate. non-halogenated aromatic phosphate esters such as 1,3-phenylene bisphosphate, hydroxyphenyl diphenyl phosphate, octyl diphenyl phosphate, 2-ethylhexyl diphenyl phosphate, and tetrakis(2,6-dimethylphenyl)-1,3-phenylene bisphosphate; and halogenated aliphatic phosphate esters such as tris(1-chloro-2-propyl)phosphate, tris(1,3-dichloro-2-propyl)phosphate, and tris[3-bromo-2,2-bis(bromomethyl)propyl]phosphate.
[0098] Examples of polyphosphates include ammonium polyphosphate and melamine polyphosphate.
[0099] Examples of phosphinates include dialkylphosphinates such as aluminum tris(diethylphosphinate), zinc bis(diethylphosphinate), aluminum tris(methylethylphosphinate), zinc bis(methylethylphosphinate), and titanium tetrakis(diethylphosphinate); and diarylphosphinates such as zinc bis(diphenylphosphinate) and titanium tetrakis(diphenylphosphinate).
[0100] Examples of the phosphinic acid ester include dialkylphosphinic acid esters such as methyl dimethylphosphinate, ethyl dimethylphosphinate, ethyl diethylphosphinate, vinyl diethylphosphinate, and phenyl diethylphosphinate; non-cyclic diarylphosphinic acid esters such as phenyl diphenylphosphinate, methyl diphenylphosphinate, and ethyl diphenylphosphinate; 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphinic acid esters; 10-(1,4-dihydroxy-2-naphthyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-(2,5-dihydroxybiphenyl-4-yl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-[2,4-di(glycidyloxy)phenyl]-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, etc. Cyclic diarylphosphinic acid esters of the above; cyclic monoarylphosphinic acid esters such as 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide; 9,10-dihydro-10-benzyl-9-oxa-10-phosphaphenanthrene-10-oxide, 10-[2,3-bis(2-hydroxyethoxycarbonyl)propyl]-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide or polyether polycondensates thereof cyclic arylalkylphosphinic acid esters such as 10-(2-cyanoethyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 10-[2-(3,4-epoxycyclohexyl)ethyl]-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 10-(3-glycidyloxypropyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0101] Examples of the phosphonate include zinc methanephosphonate, zinc ethylphosphonate, zinc butylphosphonate, and zinc phenylphosphonate.
[0102] Examples of phosphonate esters include aliphatic phosphonate esters such as diphenyl methylphosphonate, dibutyl butylphosphonate, diethyl ethylphosphonate, diethyl (methoxymethyl)phosphonate, and diethyl vinylphosphonate; and aromatic phosphonate esters such as diethyl phenylphosphonate, divinyl phenylphosphonate, and diallyl phenylphosphonate.
[0103] It is particularly preferred that the (D) flame retardant contains a phenolic hydroxyl group-containing phosphinic acid ester. The phenolic hydroxyl group equivalent of the phenolic hydroxyl group-containing phosphorus-based flame retardant is not particularly limited, but is preferably 80 g / eq. to 1,000 g / eq., more preferably 100 g / eq. to 500 g / eq., even more preferably 110 g / eq. to 300 g / eq., even more preferably 120 g / eq. to 200 g / eq., and preferably 130 g / eq. to 180 g / eq. The phenolic hydroxyl group equivalent is the mass of the phosphorus-based flame retardant per phenolic hydroxyl group equivalent. The phenolic hydroxyl group-containing phosphinic acid ester may have a function of curing the (B1) epoxy resin, like the (B2) epoxy resin curing agent.
[0104] (D) Examples of commercially available flame retardants include "SPH-100", "SPS-100", "SPB-100", and "SPE-100" (phosphazenes) manufactured by Otsuka Chemical Co., Ltd.; "FP-100", "FP-110", "FP-300", and "FP-400" (phosphazenes) manufactured by Fushimi Pharmaceutical Co., Ltd.; "HCA-NQ", "HCA-HQ", and "HCA-HQ-HST" (phosphinic acid esters (containing phenolic hydroxyl groups)) manufactured by Sankosha; and "PX-200", "PX-201", "PX-202", "CR-733S", "CR-741", and "CR-747" (phosphate esters) manufactured by Daihachi Chemical Industry Co., Ltd.
[0105] The content of the (D) flame retardant in the resin composition is not particularly limited, but is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, even more preferably 3% by mass or less, and particularly preferably 2% by mass or less, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass. The lower limit of the content of the (D) flame retardant in the resin composition is not particularly limited, but is, for example, 0% by mass or more, 0.001% by mass or more, preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.1% by mass or more, and particularly preferably 0.5% by mass or more, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass.
[0106] <(E) Thermoplastic resin> The resin composition of the present invention may further contain a thermoplastic resin (E) as an optional component. The thermoplastic resin (E) is a component other than the epoxy resin (B1) explained above.
[0107] Examples of the (E) thermoplastic resin include polyimide resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. In one embodiment, the (E) thermoplastic resin preferably contains a thermoplastic resin selected from the group consisting of polyimide resin and phenoxy resin, and more preferably contains a phenoxy resin. The (E) thermoplastic resin may be used alone or in combination of two or more kinds.
[0108] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.
[0109] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.
[0110] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.
[0111] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.
[0112] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.
[0113] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.
[0114] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.
[0115] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.
[0116] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.
[0117] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.
[0118] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include Mitsubishi Gas Chemical's "FPC0220," Asahi Kasei Chemical's "T6002" and "T6001" (polycarbonate diols), and Kuraray's "C-1090," "C-2090," and "C-3090" (polycarbonate diols). Specific examples of polyether ether ketone resins include Sumitomo Chemical's "Sumiploy K."
[0119] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.
[0120] From the viewpoint of further improving film formability, the weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.
[0121] The content of the (E) thermoplastic resin in the resin composition is not particularly limited, but when the components other than the (A) organic solvent in the resin composition are taken as 100 mass%, it may be preferably 20 mass% or less, more preferably 15 mass% or less, even more preferably 10 mass% or less, even more preferably 5 mass% or less, and particularly preferably 3 mass% or less. The lower limit of the content of the (E) thermoplastic resin in the resin composition is not particularly limited, but when the components other than the (A) organic solvent in the resin composition are taken as 100 mass%, it is, for example, 0 mass% or more, 0.01 mass% or more, preferably 0.1 mass% or more, more preferably 0.5 mass% or more, even more preferably 1 mass% or more, and particularly preferably 1.5 mass% or more.
[0122] <(F) Curing accelerator> The resin composition of the present invention may further contain, as an optional component, a curing accelerator (F), which functions as a curing catalyst for accelerating the curing of the epoxy resin (B1).
[0123] Examples of the (F) curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. The (F) curing accelerator preferably contains a curing accelerator selected from imidazole-based curing accelerators and amine-based curing accelerators, and more preferably contains an amine-based curing accelerator. The (F) curing accelerator may be used alone or in combination of two or more.
[0124] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate ... aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.
[0125] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].
[0126] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.
[0127] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.
[0128] As the imidazole-based curing accelerator, commercially available products may be used, for example, "1B2PZ", "2MZA-PW", "2PHZ-PW", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.
[0129] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.
[0130] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.
[0131] As the amine-based curing accelerator, commercially available products may be used, for example, "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.
[0132] The content of the (F) curing accelerator in the resin composition is not particularly limited, but is preferably 5% by mass or less, more preferably 1% by mass or less, even more preferably 0.5% by mass or less, and particularly preferably 0.2% by mass or less, when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass. The lower limit of the content of the (F) curing accelerator in the resin composition is not particularly limited, but may be, for example, 0% by mass or more, 0.001% by mass or more, 0.01% by mass or more, 0.05% by mass or more, etc., when the components other than the (A) organic solvent in the resin composition are taken as 100% by mass.
[0133] <(G) Other Additives> The resin composition of the present invention may further contain any additive. Examples of such additives include radical polymerizable compounds having a vinylphenyl group, an acryloyl group, a methacryloyl group, a maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group), etc.; radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; organic fillers such as rubber particles; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as bentone and montmorillonite; silicone-based leveling agents, acrylic polymer-based leveling agents, and other ... Examples of the additives include antifoaming agents such as acrylic antifoaming agents, fluorine antifoaming agents, and vinyl resin antifoaming agents; ultraviolet absorbers such as benzotriazole ultraviolet absorbers; adhesion improvers such as urea silane; adhesion imparting agents such as triazole adhesion imparting agents, tetrazole adhesion imparting agents, and triazine adhesion imparting agents; antioxidants such as hindered phenol antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine surfactants and silicone surfactants; dispersants such as phosphate ester dispersing agents, polyoxyalkylene dispersing agents, acetylene dispersing agents, silicone dispersing agents, anionic dispersing agents, and cationic dispersing agents; stabilizers such as borate stabilizers, titanate stabilizers, aluminate stabilizers, zirconate stabilizers, isocyanate stabilizers, carboxylic acid stabilizers, and carboxylic anhydride stabilizers. (G) Other additives may be used alone or in combination of two or more in any ratio. (G) The content of other additives can be appropriately determined by one skilled in the art.
[0134] <Method of producing resin composition> The resin composition of the present invention can be produced, for example, by adding (A) an organic solvent, (B) a thermosetting resin, (C) an inorganic filler, if necessary (D) a flame retardant, if necessary (E) a thermoplastic resin, if necessary (F) a curing accelerator, and if necessary (G) other additives to an arbitrary preparation vessel in any order and / or all at once and mixing them. In addition, the temperature can be appropriately set during the process of adding and mixing each component, and heating and / or cooling may be performed temporarily or throughout. In addition, during or after the process of adding and mixing, the resin composition may be stirred or shaken using a stirring device or shaking device such as a mixer to disperse it uniformly. In addition, degassing may be performed under low pressure conditions such as under vacuum at the same time as stirring or shaking.
[0135] <Characteristics of resin composition> The resin composition of the present invention comprises (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, the (A) component comprises (A1) an organic solvent having a solubility in water of 0.6 g / L or more and less than 15 g / L at 20° C., the content of the (A1) component is 35% by mass or more when the (A) component in the resin composition is taken as 100% by mass, and the content of the (C) component is 40% by mass or more when the components other than the (A) component in the resin composition are taken as 100% by mass. With such a resin composition, it is possible to suppress the occurrence of unevenness after lamination.
[0136] The resin composition of the present invention may have the characteristic of being able to suppress the occurrence of unevenness after lamination. Thus, in one embodiment, as in the following Test Example 2, when a resin sheet obtained from the resin composition of the present invention is laminated on an inner layer substrate, and then the insulating layer (cured product) around the inner layer substrate is observed for unevenness (dents), no unevenness (dents) is observed and the surface is completely uniform, or unevenness (dents) is observed only in a portion 1 cm from the outer periphery of the laminated portion, and the portion inside the portion may have a completely uniform surface.
[0137] In one embodiment, the resin composition of the present invention may be characterized by a low melt viscosity after drying. Therefore, the resin composition has excellent circuit embedding properties when laminated. In one embodiment, the minimum melt viscosity of the resin composition after drying at 60°C to 200°C measured as in the following Test Example 1 may be preferably 10000 poise or less, more preferably 7000 poise or less, even more preferably 5000 poise or less, and particularly preferably 4000 poise or less. The lower limit is not particularly limited, but from the viewpoint of maintaining the thickness stability of the resin composition layer, it may be preferably 50 poise or more, more preferably 100 poise or more, even more preferably 200 poise or more, even more preferably 300 poise or more, and particularly preferably 400 poise or more.
[0138] In one embodiment, the cured product (insulating layer) obtained from the resin composition of the present invention may be characterized by excellent mechanical strength. Thus, in one embodiment, the elongation at break of the cured product (insulating layer) measured at 23°C in accordance with the Japanese Industrial Standard JIS K7127 as in Test Example 3 below is not particularly limited, but may be preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, even more preferably 1.8% or more, and particularly preferably 2% or more. The upper limit of the elongation at break is not particularly limited, but may usually be 10% or less, 5% or less, etc.
[0139] <Applications of resin composition> The resin composition of the present invention can be suitably used as a resin composition for insulating purposes, particularly as a resin composition for forming an insulating layer. Specifically, it can be suitably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer for forming a conductor layer) for forming a conductor layer (including a rewiring layer) formed on an insulating layer. In addition, in a printed wiring board described later, it can be suitably used as a resin composition for forming an insulating layer of a printed wiring board (resin composition for forming an insulating layer of a printed wiring board). The resin composition of the present invention can also be used in a wide range of applications requiring a resin composition, such as a resin sheet, a sheet-like laminate material such as a prepreg, a solder resist, an underfill material, a die bonding material, a semiconductor encapsulant, a hole filling resin, and a component embedding resin.
[0140] In addition, for example, when a semiconductor chip package is manufactured through the following steps (1) to (6), the resin composition of the present invention can be suitably used as a resin composition for a rewiring formation layer (resin composition for forming a rewiring formation layer) as an insulating layer for forming a rewiring layer, and as a resin composition for sealing a semiconductor chip (resin composition for sealing a semiconductor chip). When a semiconductor chip package is manufactured, a rewiring layer may be further formed on the sealing layer. (1) A step of laminating a temporary fixing film onto a substrate; (2) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (3) forming an encapsulation layer on the semiconductor chip; (4) peeling the substrate and the temporary fixing film from the semiconductor chip; (5) forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film have been peeled off; and (6) A process of forming a rewiring layer as a conductor layer on the rewiring formation layer.
[0141] Furthermore, the resin composition of the present invention provides an insulating layer with good component embedding properties, and therefore can be suitably used when the printed wiring board is a circuit board with built-in components.
[0142] <Sheet-type laminated material> The resin composition of the present invention can be used by coating in the form of a varnish, but from an industrial perspective, it is generally preferred to use the resin composition in the form of a sheet-like laminate material containing the resin composition.
[0143] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.
[0144] In one embodiment, the resin sheet comprises a support and a layer of a resin composition provided on the support, and the layer of the resin composition is formed from the resin composition of the present invention.
[0145] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of making the printed wiring board thinner and being able to provide a cured product with excellent insulating properties even if the cured product of the resin composition is a thin film. The lower limit of the thickness of the resin composition layer is not particularly limited, but can usually be 5 μm or more, 10 μm or more, etc.
[0146] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.
[0147] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.
[0148] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.
[0149] The surface of the support which is to be bonded to the layer of the resin composition may be subjected to a matte treatment, a corona treatment or an antistatic treatment.
[0150] In addition, as the support, a support with a release layer having a release layer on the surface to be bonded to the layer of the resin composition may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.
[0151] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.
[0152] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, adhesion of dirt and the like to the surface of the resin composition layer and scratches can be suppressed.
[0153] The resin sheet can be produced, for example, by applying a varnish-like resin composition onto a support using a die coater or the like, and then drying the applied composition to form a resin composition layer.
[0154] Drying may be performed by a known method such as heating or hot air blowing. Drying conditions are not particularly limited, but the content of the organic solvent in the resin composition layer is preferably 20% by mass or less, more preferably 15% by mass or less, even more preferably 10% by mass or less, even more preferably 7% by mass or less, and particularly preferably 5% by mass or less. Although it varies depending on the boiling point of the organic solvent in the resin composition (varnish-like) and the thickness of the resin composition layer, for example, drying at 50°C to 200°C, preferably 50°C to 150°C, for 3 to 10 minutes can form a film-like resin composition layer.
[0155] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it can be used by peeling off the protective film.
[0156] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition of the present invention.
[0157] The sheet-like fiber substrate used for the prepreg is not particularly limited, and can be a substrate commonly used for prepreg, such as glass cloth, aramid nonwoven fabric, liquid crystal polymer nonwoven fabric, etc. From the viewpoint of thinning the printed wiring board, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited. It is usually 10 μm or more.
[0158] The prepreg can be produced by a known method such as a hot melt method or a solvent method.
[0159] The thickness of the prepreg may be in the same range as the layer of the resin composition in the resin sheet described above.
[0160] The sheet-like laminate material of the present invention can be suitably used for forming an insulating layer of a printed wiring board (for an insulating layer of a printed wiring board), and can be more suitably used for forming an interlayer insulating layer of a printed wiring board (for an interlayer insulating layer of a printed wiring board).
[0161] <Printed wiring board> The printed wiring board of the present invention includes an insulating layer made of a cured product obtained by curing the resin composition of the present invention.
[0162] The printed wiring board can be produced, for example, by using the above-mentioned resin sheet by a method including the following steps (I) and (II). (I) A step of laminating a resin sheet onto an inner layer substrate so that a layer of a resin composition of the resin sheet is bonded to the inner layer substrate. (II) A step of curing (e.g., heat curing) the layer of the resin composition to form an insulating layer.
[0163] The "inner layer substrate" used in step (I) is a member that becomes the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be formed during the manufacture of a printed wiring board is also included in the "inner layer substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.
[0164] The lamination of the inner layer substrate and the resin sheet can be carried out, for example, by thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression member not directly onto the resin sheet, but via an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate.
[0165] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination may be performed under reduced pressure conditions, preferably at a pressure of 26.7hPa or less.
[0166] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.
[0167] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.
[0168] The support may be removed between step (I) and step (II) or after step (II).
[0169] In step (II), the layer of the resin composition is cured (for example, thermally cured) to form an insulating layer made of a cured product of the resin composition. The curing conditions for the layer of the resin composition are not particularly limited, and conditions that are usually adopted when forming an insulating layer for a printed wiring board may be used.
[0170] For example, the thermal curing conditions of the resin composition layer vary depending on the type of resin composition, etc., but in one embodiment, the curing temperature is preferably 120° C. to 240° C., more preferably 150° C. to 220° C., and even more preferably 170° C. to 210° C. The curing time is preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.
[0171] Before the layer of the resin composition is thermally cured, the layer of the resin composition may be preheated at a temperature lower than the curing temperature. For example, prior to thermally curing the layer of the resin composition, the layer of the resin composition may be preheated at a temperature of 50° C. to 120° C., preferably 60° C. to 115° C., more preferably 70° C. to 110° C. for 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.
[0172] In manufacturing a printed wiring board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art for use in manufacturing printed wiring boards. When the support is removed after step (II), the support may be removed between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). In addition, the formation of the insulating layer and the conductor layer in steps (II) to (V) may be repeated to form a multilayer wiring board, as necessary.
[0173] In another embodiment, the printed wiring board of the present invention can be manufactured using the above-mentioned prepreg. The manufacturing method is basically the same as when a resin sheet is used.
[0174] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.
[0175] Step (IV) is a step of roughening the insulating layer. Usually, smears are also removed in this step (IV). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.
[0176] The swelling liquid used in the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, etc., and is preferably an alkaline solution, and more preferably a sodium hydroxide solution or a potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes, for example. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.
[0177] The oxidizing agent used in the roughening treatment is not particularly limited, but examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.
[0178] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product such as "Reduction Solution Securigant P" manufactured by Atotech Japan can be mentioned.
[0179] The treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.
[0180] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is not particularly limited, but is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.
[0181] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.
[0182] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.
[0183] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.
[0184] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.
[0185] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.
[0186] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the surface of the exposed layer of the resin composition. The layer of the resin composition and the metal foil may be laminated by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.
[0187] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.
[0188] <Semiconductor device> The semiconductor device of the present invention includes the printed wiring board of the present invention. The semiconductor device of the present invention can be manufactured by using the printed wiring board of the present invention.
[0189] Examples of the semiconductor device include various semiconductor devices used in electric appliances (for example, computers, mobile phones, digital cameras, and televisions) and vehicles (for example, motorcycles, automobiles, trains, ships, and aircraft). EXAMPLES
[0190] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature condition is room temperature (23°C), and unless otherwise specified, the pressure condition is atmospheric pressure (1 atm).
[0191] <Example 1> Thirty parts of bisphenol A type epoxy resin ("828US" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent approximately 180 g / eq.) and 30 parts of biphenyl type epoxy resin ("NC3000H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent approximately 269 g / eq.) were heated and dissolved in 55 parts of MAK (methyl-n-amyl ketone, solubility in water 4.2 g / L (20°C)) with stirring, and then cooled to room temperature. The mixture was mixed with 260 parts of spherical silica (solid silica) particles (average particle size 0.5 μm, Admatechs' SO-C2) that had been surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical's KBM573), 3 parts of a flame retardant (Sanko's HCA-HQ-HST, 10-(2,5-dihydroxyphenyl)-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, average particle size 1.5 μm, phenolic hydroxyl group equivalent approx. 162 g / eq.), and 2-methoxypropanol (water solubility 1000 g / L (20 ℃) solution), 14 parts of an active ester compound (DIC Corporation "HPC-8000-65T", active group equivalent of about 223, toluene (solubility in water 0.5 g / L (20 ° C)) solution of 65 mass% non-volatile components), 40 parts of a phenoxy resin (Mitsubishi Chemical Corporation "YX6954BH30", a solution in which MEK (solubility in water 29 g / L (20 ° C)) with a non-volatile component of 30 mass% and Anone (cyclohexanone, solubility in water 25 g / L (20 ° C)) are mixed at a ratio of 1: 1), and 6 parts of a curing accelerator ("DMAP", 4-dimethylaminopyridine, MEK (solubility in water 29 g / L (20 ° C)) solution of 5 mass% solids) were mixed and uniformly dispersed with a high-speed rotating mixer to prepare a varnish-like resin composition.
[0192] (Method for measuring the average particle size of inorganic fillers) 100 mg of inorganic filler and 10 g of methyl ethyl ketone were weighed into a vial and dispersed by ultrasonic waves for 10 minutes. Using a laser diffraction particle size distribution measuring device (HORIBA, Ltd.'s "LA-960"), the particle size distribution of the inorganic filler was measured on a volume basis using a flow cell method with blue and red light source wavelengths. From the particle size distribution obtained, the average particle size of the inorganic filler was calculated as the median diameter.
[0193] (Method for measuring average porosity of inorganic filler) The density of the inorganic filler was measured using a true density measuring device (QUANTACHROME's "ULTRAPYCNOMETER 1000"). In this measurement, nitrogen was used as the measurement gas. The measured density (measured value) D M (g / cm 3 ) and the material density (theoretical value) D of the inorganic material (silica) that forms the inorganic filler T (g / cm 3 ) was used to measure the average porosity of the inorganic filler according to the above formula (I). In the above formula (I), the material density (theoretical value) of silica as an inorganic material is 2.2 g / cm 3 It was decided.
[0194] <Example 2> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 55 parts of CHXA (cyclohexanol acetate, solubility in water 2 g / L (20° C.)) was used instead of 55 parts of MAK.
[0195] <Example 3> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 55 parts of BMGAC (ethylene glycol monobutyl ether acetate, solubility in water 10 g / L (20° C.)) was used instead of 55 parts of MAK.
[0196] <Example 4> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 120 parts of spherical silica (solid silica) particles (average particle size 0.078 μm, Denki Kagaku Kogyo Co., Ltd. "UFP-30") surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM573") were used instead of 260 parts of spherical silica (solid silica) particles (average particle size 0.5 μm, Admatechs Co., Ltd. "SO-C2") surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM573").
[0197] <Example 5> A varnish-like resin composition was prepared in the same manner as in Example 4, except that the amount of MAK used was changed to 35 parts and 20 parts of BMGAC (ethylene glycol monobutyl ether acetate, solubility in water 10 g / L) was further used.
[0198] <Example 6> A varnish-like resin composition was prepared in the same manner as in Example 1, except that the amount of spherical silica (solid silica) particles (average particle size 0.5 μm, Admatechs' SO-C2) surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical's KBM573) was changed from 260 parts to 80 parts, and 90 parts of hollow silica particles (JGC Catalysts and Chemicals' BA-S, average particle size 2.6 μm, porosity 25% by volume) surface-treated with an aminosilane coupling agent (Shin-Etsu Chemical's KBM573) were used.
[0199] <Example 7> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 30 parts of a naphthol-type epoxy resin ("ESN475V" manufactured by Nippon Steel Chemical & Material Co., Ltd., epoxy equivalent: 332 g / eq.) was used instead of 30 parts of a biphenyl-type epoxy resin ("NC3000H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: approximately 269 g / eq.).
[0200] <Example 8> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 30 parts of a bixylenol-type epoxy resin ("YX4000HK" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent: approximately 185 g / eq.) was used instead of 30 parts of a biphenyl-type epoxy resin ("NC3000H" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: approximately 269 g / eq.).
[0201] <Comparative Example 1> A varnish-like resin composition was prepared in the same manner as in Example 1, except that 55 parts of solvent naphtha was used instead of 55 parts of MAK.
[0202] <Comparative Example 2> A varnish-like resin composition was prepared in the same manner as in Example 4, except that 55 parts of solvent naphtha was used instead of 55 parts of MAK.
[0203] <Comparative Example 3> A varnish-like resin composition was prepared in the same manner as in Example 4, except that 55 parts of MAK was not used and 55 parts of toluene (solubility in water: 0.5 g / L (20° C.)) was further added.
[0204] <Comparative Example 4> A varnish-like resin composition was prepared in the same manner as in Example 4, except that 55 parts of PGMEA (propylene glycol monomethyl ether acetate, solubility in water 198 g / L (20° C.)) was used instead of 55 parts of MAK.
[0205] <Production Example 1> A PET film with an alkyd resin-based release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. On the release layer of the support, the varnish-like resin compositions prepared in the Examples and Comparative Examples were uniformly applied so that the thickness of the resin composition layer after drying was 40 μm, and the resulting mixture was dried at 80 to 120° C. (average 100° C.) for 5 minutes to prepare a resin sheet.
[0206] (Method of Analyzing Organic Solvents in Resin Composition Layer of Resin Sheet by GC / MS (Gas Chromatography Mass Spectrometry)) A 5 mg portion of the resin composition layer was measured from the resin sheet prepared in Preparation Example 1, and the measured sample was processed in an oven at 250° C. for 10 minutes using a GCMS-QP2020-NX (manufactured by Shimadzu Corporation), and measured under conditions of a sample line temperature of 260° C., a transfer line temperature of 260° C., and a cycle time of 55 minutes. The type of solvent was identified from each detected peak, and the type and content of the organic solvent contained in the resin sheet of the support-attached resin sheet (i.e., each organic solvent / total (A) component) were analyzed by comparing the type of solvent with the previously prepared calibration curve.
[0207] (Method for measuring weight loss rate of resin composition layer of resin sheet due to heat treatment) The resin sheet prepared in Preparation Example 1 was cut into 10 cm x 10 cm pieces, which were placed in a desiccator together with thoroughly dried silica gel and left for 30 minutes. Thereafter, the mass (g) of the resin sheet was measured with the protective film peeled off, and the value was taken as α1 (g). Next, the resin sheet was heated in an oven at 190 ° C. for 30 minutes, and after cooling in a desiccator together with silica gel for 30 minutes as before, the mass (g) of the resin sheet was measured again, and the value was taken as α2 (g). In addition, only the support was cut into 10 cm x 10 cm pieces, which were left in a desiccator for 30 minutes, and the mass (g) of the support was measured, and the value was taken as β (g). The weight reduction rate α (i.e., total (A) components / total components) (%) of the resin composition layer when the resin sheet was heat-treated at 190 ° C. for 30 minutes was calculated from the following formula (A).
[0208]
number
[0209] <Test Example 1: Measurement of minimum melt viscosity> The melt viscosity of the resin composition layer of the resin sheet produced in Production Example 1 was measured. Using UBM's "Rheosol-G3000," the melt viscosity was measured using 1 g of resin and parallel plates with a diameter of 18 mm under the measurement conditions of a starting temperature of 60°C to 200°C, a heating rate of 5°C / min, a measurement temperature interval of 2.5°C, and a vibration of 1 Hz / deg, and the minimum melt viscosity (Poise) within the measurement temperature range was evaluated.
[0210] <Test Example 2: Evaluation of unevenness on cured substrate> Both sides of a glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.4 mm, Panasonic "R1515A") with an inner layer circuit formed were etched 1 μm with a microetching agent (Mec "CZ8101") to roughen the copper surface.
[0211] The 40 μm thick resin sheet prepared in Preparation Example 1 was laminated on both sides of the inner layer substrate using a batch type vacuum pressure laminator (Nikko Materials Co., Ltd., 2-stage build-up laminator "CVP700"). Lamination was performed by reducing the pressure for 30 seconds to adjust the air pressure to 13 hPa or less, and then pressing at 120°C and a pressure of 0.74 MPa for 30 seconds. Next, a heat press was performed at 100°C and a pressure of 0.5 MPa for 60 seconds.
[0212] Thereafter, the inner layer substrate laminated with the resin sheet was placed in an oven at 130° C. and heated for 30 minutes, and then transferred to an oven at 170° C. and heated for 30 minutes to thermally cure the resin composition layer and form an insulating layer. Thereafter, the support was peeled off to obtain a cured substrate having the insulating layer, the inner layer substrate, and the insulating layer in this order.
[0213] For both sides of the cured substrate, the surface uniformity of the area where the resin sheet was laminated (the surface opposite to the laminated plate) was visually observed and evaluated according to the following evaluation criteria.
[0214] Evaluation criteria "Good": No unevenness (dents) are observed and the surface is completely uniform, or unevenness (dents) are observed only in the area 1 cm from the outer periphery of the area where the resin sheet is laminated, and the area inside is a completely uniform surface. "X": When uneven areas are observed within 1 cm of the outer periphery of the resin sheet laminated area
[0215] <Test Example 3: Measurement of elongation at break> The 40 μm thick resin sheet produced in Production Example 1 was heated at 200° C. for 90 minutes to thermally cure the resin composition layer, and then the support was peeled off. The resulting cured product is referred to as the “cured product for evaluation.” The cured product for evaluation was subjected to a tensile test using a Tensilon universal testing machine (manufactured by Orientec Co., Ltd., “RTC-1250A”) in accordance with the Japanese Industrial Standards (JIS K7127) to measure the elongation at break (%) at 23° C.
[0216] The amounts of raw materials used in the resin compositions of the Examples and Comparative Examples, and the measurement results and evaluation results of the Test Examples are summarized in Table 1 below.
[0217] [Table 1]
[0218] The results shown in Table 1 above show that when a resin composition containing (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L is used, the occurrence of unevenness after lamination can be suppressed compared to when no organic solvent is used.
Claims
1. A resin composition comprising (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, The component (A) includes (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L, The component (B) contains an epoxy resin, When the resin composition is dried to form a resin composition layer, The content of the (A1) component in the resin composition layer is 50% by mass or more and 95% by mass or less, when the content of the (A) component in the resin composition layer is 100% by mass, A resin composition (excluding resin compositions containing a resin having an epoxy group and a functional group that reacts with a radically polymerizable functional group) in which the content of the (C) component in the resin composition layer is 40 mass% or more, when the components other than the (A) component in the resin composition layer are taken as 100 mass%.
2. 2. The resin composition according to claim 1, wherein the component (A1) contains an organic solvent having a boiling point of 130° C. to 200° C. at 760 mmHg.
3. 3. The resin composition according to claim 1, wherein the component (A1) comprises an organic solvent selected from the group consisting of ketone-based solvents, ester-based solvents, and glycol ether ester-based solvents.
4. The resin composition according to any one of claims 1 to 3, wherein the component (A) further comprises (A2) an organic solvent having a solubility in water at 20°C of 15 g / L or more and less than 150 g / L.
5. The resin composition according to claim 4 , wherein the component (A2) comprises a ketone-based solvent.
6. The resin composition according to any one of claims 1 to 5, wherein the component (A) further comprises (A3) an organic solvent having a solubility in water at 20°C of less than 0.6 g / L.
7. The resin composition according to any one of claims 1 to 6, wherein the component (A) further comprises (A4) an organic solvent having a solubility in water at 20°C of 150 g / L or more.
8. A resin composition described in any one of claims 1 to 7, wherein the (A) component includes (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L, (A2) an organic solvent having a solubility in water at 20°C of 15 g / L or more and less than 150 g / L, (A3) an organic solvent having a solubility in water at 20°C of less than 0.6 g / L, and (A4) an organic solvent having a solubility in water at 20°C of 150 g / L or more.
9. The resin composition according to any one of claims 1 to 8, wherein the component (B) further comprises an active ester-based curing agent.
10. The resin composition according to any one of claims 1 to 9, wherein the component (B) further comprises a phenol-based curing agent.
11. A cured product of the resin composition according to any one of claims 1 to 10.
12. A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of claims 1 to 11.
13. A semiconductor device comprising the printed wiring board according to claim 12.
14. A support; A resin composition layer provided on the support, the resin composition layer including (A) an organic solvent, (B) a thermosetting resin, and (C) an inorganic filler, The component (A) includes (A1) an organic solvent having a solubility in water at 20°C of 0.6 g / L or more and less than 15 g / L, The component (B) contains an epoxy resin, The content of the component (A1) is 50% by mass or more and 95% by mass or less, when the content of the component (A) in the resin composition layer is 100% by mass, A resin composition layer in which the content of the component (C) is 40% by mass or more, when the content of the components other than the component (A) in the resin composition layer is 100% by mass; (However, a resin composition layer containing a resin having an epoxy group and a functional group that reacts with a radical polymerizable functional group is excluded.)
15. A resin sheet as described in claim 14, wherein the minimum melt viscosity of the resin composition layer at 60°C to 200°C is 10,000 poise or less.
16. A resin sheet as described in claim 14 or 15, wherein the minimum melt viscosity of the resin composition layer at 60°C to 200°C is 50 poise or more.
17. A method for producing a printed wiring board, comprising the following steps (I) and (II): (I) A step of laminating the resin sheet according to any one of claims 14 to 16 so that a layer of the resin composition of the resin sheet is bonded to an inner layer substrate. (II) A step of curing the layer of the resin composition to form an insulating layer
Citation Information
Patent Citations
Method for manufacturing multilayer printed wiring board
JP2014229840A
Curable resin composition, dry film, cured article and printed wiring board
JP2016113608A
Resin sheet
JP2017177461A
Resin composition
JP2018044040A
Resin composition
JP2019035056A